1989
DOI: 10.4319/lo.1989.34.2.0397
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton abundance in the lower Orinoco River, Venezuela

Abstract: Zooplankton were sampled quantitatively in the lower Orinoco River and three major tributaries (Apure, Caura, Caroni). Dominant taxa were euplanktonic, which suggests origin from standing waters. In the Orinoco, densities for rotifers (mean, 7.6 ind. liter -I) were greater than those for cladocerans (0.9 ind. liter-I) or copepods (1.2 ind. liter-'), but cladocerans accounted for more than half oftotal biomass (0.5 kg C liter -I). Average tributary contributions to zooplankton transport in the lower Orinoco (87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 23 publications
3
51
1
1
Order By: Relevance
“…Compared to mean density of zooplankton in the Orinoco main stem (Saunders & Lewis 1989, Vâs-quez & Rey 1989, mean density in the lakes was -100 times higher than in the river. A similar value was reported by Hamilton et al (1990) from ano ther Orinoco fioodplain lake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to mean density of zooplankton in the Orinoco main stem (Saunders & Lewis 1989, Vâs-quez & Rey 1989, mean density in the lakes was -100 times higher than in the river. A similar value was reported by Hamilton et al (1990) from ano ther Orinoco fioodplain lake.…”
Section: Discussionmentioning
confidence: 99%
“…A similar value was reported by Hamilton et al (1990) from ano ther Orinoco fioodplain lake. Considering the extension of the fioodplain and the high abundance of zooplankton found in these areas, the contribu tion of zooplankton biomass from fioodplain areas to the river is very small (Saunders & Lewis 1989). Hamilton et al (1990) ascribed the absence of a significant export of zooplankton as a consequence of retention of planktonic organisms by aquatic macrophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Another littoral species common on the floodplain is Ilyocryptus spinifer. The pelagic species B. deitersi, B. hagmanni, C. cornuta, and M. minuta are also frequent and often dominant on other floodplains (Brandorff et al, 1982;Robertson & Hardy, 1984;Saunders III & Lewis-Jr., 1989;Paggi & José de Paggi, 1990;Bozelli et al, 1992;Sendacz, 1997).…”
Section: Bosmina Tubicen Brehm 1939mentioning
confidence: 99%
“…According to RZOSKA (1978), zooplankton reproduction is unlikely at water velocities > 0.4 m/s (THORP and CASPER, 2003). SAUNDERS and LEWIS (1989) reported an inverse relationship between egg rations of rotifers and water velocity. The above authors observed no egg-carrying individuals at current velocities > 1.5 m/s (RECKNDORFER et al, 1999).…”
Section: Taxonomic Compositionmentioning
confidence: 99%